2011
DOI: 10.1108/17590831111139893
|View full text |Cite
|
Sign up to set email alerts
|

The application of Halal in supply chain management: in‐depth interviews

Abstract: Purpose -The paper aims to describe the basic requirements of Halal food supply chains in order to ensure the integrity of Halal food at the point of consumption, which is an obligation for Muslims. Design/methodology/approach -This exploratory research paper is based on in-depth interviews to better understand what is Halal, the Islamic sources that are essential for Halal supply chains, and identify the guidelines and principles which are essential for the integrity of Halal supply chains. Findings -Halal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
300
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(312 citation statements)
references
References 11 publications
3
300
0
9
Order By: Relevance
“…Halal certification is very commonly needed in the food, beverage, hospitality and restaurant industries regarding the importance of knowledge about halal restrictions for Islamic consumers [7]. In some studies found also the implementation of halal principles in the supply chain, namely by avoiding direct contact with the Haram object, overcoming the risk of contamination and ensure it is in accordance with Muslim consumer perceptions [8]. Even other religious or non-Muslim consumers understand the importance of halal principles that also address health issues, food safety and environmentally friendly ways of production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Halal certification is very commonly needed in the food, beverage, hospitality and restaurant industries regarding the importance of knowledge about halal restrictions for Islamic consumers [7]. In some studies found also the implementation of halal principles in the supply chain, namely by avoiding direct contact with the Haram object, overcoming the risk of contamination and ensure it is in accordance with Muslim consumer perceptions [8]. Even other religious or non-Muslim consumers understand the importance of halal principles that also address health issues, food safety and environmentally friendly ways of production [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies are carried out on the requirement and benefits of the traceability system [4,27,28]. However, it is difficult to find literature related to the implementation of traceability system in Halal context.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Halal food industries are very important for Malaysians as 60% of its population are Muslim and many Halal manufacturing are dominated by nonMuslim manufacturers in this country (Tieman, 2011). Its government attempts to create a nodal agency to promote Malaysia as a centre for Halal foods to cover Islamic dietary requirements (Muhammad et al, 2009).…”
Section: Ajesmentioning
confidence: 99%